2000
DOI: 10.1200/jco.2000.18.10.2070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Predictive Value of Her-2/neu Overexpression and p53 Mutations in High-Risk Primary Breast Cancer Patients Treated With High-Dose Chemotherapy and Autologous Stem-Cell Transplantation

Abstract: Her-2/neu overexpression is an independent negative predictor of RFS and OS in HRPBC treated with HDCT. Its inclusion in our previously described predictive model increases the predictive capacity of this model for the low-risk subgroup. In contrast, p53 mutations lack predictive value in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 36 publications
4
46
3
1
Order By: Relevance
“…Nieto et al (1999) generated a predictive model based on tumour size, receptor status, and axillary nodal ratio; later they found HER2/neu overexpression (using monoclonal CB11 antibody-staining) as an additional independent predictor of RFS and OS primarily in an otherwise 'favourable' group of patients (Nieto et al, 2000). Using a polyclonal antibody-directed immunohistochemical stain the incidence of HER2/neu positive staining in our HRBC population was very similar to that reported in patients with stage II breast cancer (Thor et al, 1998) and to the selected, high risk population reported by Bitran et al (1996), although slightly lower then in the series by Nieto et al (1999). Since there is wide variation in the type and specificity of available antibodies and retrieving techniques, and the clinical significance of utilizing one antibody vs another is unclear (Ravdin et al, 1998), the predictive value of HER-2/neu amplification for choosing the optimal adjuvant therapy needs further validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nieto et al (1999) generated a predictive model based on tumour size, receptor status, and axillary nodal ratio; later they found HER2/neu overexpression (using monoclonal CB11 antibody-staining) as an additional independent predictor of RFS and OS primarily in an otherwise 'favourable' group of patients (Nieto et al, 2000). Using a polyclonal antibody-directed immunohistochemical stain the incidence of HER2/neu positive staining in our HRBC population was very similar to that reported in patients with stage II breast cancer (Thor et al, 1998) and to the selected, high risk population reported by Bitran et al (1996), although slightly lower then in the series by Nieto et al (1999). Since there is wide variation in the type and specificity of available antibodies and retrieving techniques, and the clinical significance of utilizing one antibody vs another is unclear (Ravdin et al, 1998), the predictive value of HER-2/neu amplification for choosing the optimal adjuvant therapy needs further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Better selection of patients for studies of future HDCT programmes, as well as other investigational approaches for women with HRBC, may be possible after validation of this and other (Nieto et al, 1999) prognostic models.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has suggested that the axillary node ratio, defined as the number of axillary nodes involved with breast cancer divided by the absolute number of axillary nodes sampled, is an independent prognostic feature concerning transplantation outcome for this patient population. 13 We report a retrospective review of 111 women with high-risk stage II/III breast cancer with at least four positive axillary nodes undergoing autologous PBPC transplantation from 1991 to June 1999.…”
mentioning
confidence: 99%
“…Some studies have addressed prognostic factors for relapse after HDC and PBPCT. 3,20,[32][33][34][35][36][37][38][39] In the analysis by Somlo et al 37 of HRBC patients treated with two different HDC, PR negativity was the only independent prognostic factor of relapse. Nieto et al 39 described a predictive model using a scoring system that include the nodal ratio, tumor size and the ER/PR status.…”
Section: Discussionmentioning
confidence: 99%